Accuracy of CT colonography in the preoperative staging of colon cancer: a prospective study of 217 patients. (24th June 2019) - Maupoey Ibáñez, J.; Pàmies Guilabert, J.; Frasson, M.; Boscà Robledo, A.; Giner Segura, F.; García‐Granero Ximénez, E.
Abstract: Aim: The purpose of the present study was to evaluate the accuracy of computed tomography colonography (CTC) in the preoperative localization and TN staging of colon cancer. CTC can be an effective technique for preoperative evaluation of colon cancer and could facilitate the selection of high‐risk patients who may benefit from neoadjuvant chemotherapy. Method: This was a prospective observational study conducted at a single tertiary‐care centre. It involved 217 patients (225 tumours) who had colon cancer and underwent preoperative CTC and elective colectomy. The radiologist determined the TNM stage using postprocessing software with multiplanar images and virtual colonoscopy. The following criteria were analysed for every colon tumour: location, size and signs of direct colon wall invasion. The histopathological findings of the surgical colectomy specimens served as the reference standard for local staging. Results: CTC detected all tumours and achieved an exact location in 208 cases (92.4%). CTC findings changed the surgical plan in 31 patients (14.3%) following colonoscopy. The accuracy in differentiating T3/T4 vs T1/T2 tumours was 87.1%, with a sensitivity and specificity of 88.5% and 84.1%, respectively (kappa = 0.71). For high‐risk tumours (T3 ≥ 5 mm and T4), CTC showed an accuracy, sensitivity and specificity of 82.7%, 86% and 80%, respectively (kappa = 0.65). The accuracy of N‐stage evaluation was 69.3%, the sensitivity 74% and the specificity 67.1% (kappa = 0.37). Conclusion: CTC provides accurate information for the assessment of tumour localization and T staging, allowing better surgical planning and also allows the selection of locally advanced tumours that may benefit from new treatments such as neoadjuvant chemotherapy.